A Study on the Correlation between the Foot Features and Gait Characteristics during Over-ground Walking - Kyung-Ryoul Mun; Choi Seon Jong; Chun, Sung kuk; Junggi Hong; Jinwook Kim (35th Conference of the International Society of Biomechanics in Sports, 2017)
We analysed the correlation between the foot features such as foot length, foot width, the height and angles of foot arch curves and gait spatiotemporal parameters. To measure the structure of the foot, we measured the height and structural variation of medial longitudinal arch(MLA) and lateral longitudinal arch(LLA) in various conditions using a ？Scanning stage？ consisting of a single depth camera and four uni-axial force sensors. The gait spatiotemporal parameters were obtained by a motion capture system from the seventeen subjects. All subjects were instructed to walk at a regular pace, and spatiotemporal gait parameters of ten strides in the middle of the walkway were measured. As a result, it has been shown that the height angle of MLA is significantly correlated with gait temporal parameters while the LLA is significantly related to gait spatial parameters.